Ensino contextualizado de área e volume de cilindro - Binotti, Andréa Magalhães (2016)
The study Geometry Metric Space is very important in high school. To observe, analyze and evaluate the student body to what I teach, we see the lack of interest and a lot of difficulties in relation to learning geometry, especially the spatial geometry. In order to stimulate the students and contribute to overcoming these difficulties we propose in this paper a contextualized teaching sequence for teaching such content. Because of the time available to carry out this project to go beyond the particular subject area and volume of right circular cylinders. The didactic sequence mix the use of official teaching materials of the State of São Paulo (Notebook student and teacher) and application activities leaves prepared for us. It consists of four lectures using the official materials, three classes for problem solving, four classes for implementation of activities leaves and two classes for socialization of results. In class prior to the implementation of activities leaves students must recognize circular cylinders that are part of everyday life, study the surface areas of concepts and volume of circular straight cylinder review simple rule of three, length measurement units, area and volume and method of rounding values. Then must solve problem situations to assess the understanding of the issues mentioned above. Regarding the implementation of activities leaves the students, in groups and with little intervention teacher, calculate the area of aluminum sheet required to build a pressure cooker and then check if the capacity specified by the manufacturer is real. They are then asked to find the minimum size of the pot with volume set, with the idea of getting material savings in manufacturing. After the implementation of activities leaves students with the mediation of the teacher, make the correction. This sequence was applied in two classes of the second high school grade of a school of the São Paulo State Education Network in a country town. It is important to note that this proposal adopts suggestions from the National Curriculum Guidelines for Secondary Education (PCNEM) and requires few resources and can be useful to other professionals. For validation of this research follow in general steps, the four phases of research methodology called Didactic Engineering.